Methodological basis for assessing the quality and effectiveness of endodontic dental care at the present stage - A. K. Iordanishvili; I. B. Salmanov; A. A. Serikov (LLC "Endo Press", 2019)
The article presents the results of the implementation of the method of internal quality control of medical care in the dental treatment-and-prophylactic institution. A methodology for assessing the quality and effectiveness of endodontic treatment of teeth with pulpitis and periodontitis is described. It was noted that competent implementation of internal quality control of endodontic care allowed departmental hospitals to increase its effectiveness a year later in the treatment of complicated forms of single-root, two and three root teeth, respectively, to 77.8%, 60.7% and 60.6% of cases with pulpitis and, respectively, up to 69.2%, 75.0% and 65.6% of cases with periodontitis.